2015
DOI: 10.1093/eurheartj/ehv560
|View full text |Cite
|
Sign up to set email alerts
|

Sex-related differences in calcific aortic stenosis: correlating clinical and echocardiographic characteristics and computed tomography aortic valve calcium score to excised aortic valve weight

Abstract: Despite the same degree of AS severity, women have less AVC and lower AVW compared with men, irrespective of valve morphology. Aortic valve calcium is correlated to excised AVW. Hypertension, diabetes, and current cigarette smoking were independently associated with AVW.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 24 publications
7
37
0
1
Order By: Relevance
“…28 Nevertheless, 3 recent studies found important differences between men and women with regard to the development, extent, and progression of aortic valve calcifications supporting sex-related differences in the mechanism of AS. [29][30][31] Our findings of distinct risk profiles between men and women with AS at a community level support this notion and call for further research in sex-specific disease mechanisms.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…28 Nevertheless, 3 recent studies found important differences between men and women with regard to the development, extent, and progression of aortic valve calcifications supporting sex-related differences in the mechanism of AS. [29][30][31] Our findings of distinct risk profiles between men and women with AS at a community level support this notion and call for further research in sex-specific disease mechanisms.…”
Section: Discussionsupporting
confidence: 72%
“…In addition, the focus of research on this topic has been to investigate sex differences in ventricular responses to pressure and volume overload posed by valvular disease rather than evaluating differences in the mechanism of AS itself 28. Nevertheless, 3 recent studies found important differences between men and women with regard to the development, extent, and progression of aortic valve calcifications supporting sex‐related differences in the mechanism of AS 29, 30, 31. Our findings of distinct risk profiles between men and women with AS at a community level support this notion and call for further research in sex‐specific disease mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…As in many adult diseases, processes that control normal embryonic processes also are involved in valve pathologies. Recent reports described dissimilarities in the ratios of fibrotic to calcified tissue in equally stenotic valves from men versus women [ 4 , 5 , 6 , 7 ]. Because TGF-β signaling is generally pro-fibrotic and BMP signaling is generally anti-fibrotic, we wondered if sex-associated changes in this balance contributed to the skewed sex distribution of valvular heart disease [ 4 , 7 , 8 , 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…That a "one size fits all" approach to cardiovascular treatment cannot work for men and women is now widely recognized [43]. [5][6][7]. We postulate that the balance of BMP/TGF-β signaling may differ in the valves from males and females.…”
Section: Crosstalk and Balancementioning
confidence: 91%
“…Recent reports described dissimilarities in the ratios of fibrotic to calcified tissue in equally stenotic valves from men versus women [4][5][6][7]. Because TGF-β signaling is generally pro-fibrotic and BMP signaling is generally anti-fibrotic, we wondered if sex-associated changes in this balance contributed to the skewed sex distribution of valvular heart disease [4,[7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%